Effect of Vestibular Rehabilitation on Spontaneous Brain Activity in Patients With Vestibular Migraine: A Resting-State Functional Magnetic Resonance Imaging Study - Liu, Li; Hu, Xiaofei; Zhang, Yixin; Pan, Qi; Zhan, Qunling; Tan, Ge; Wang, Kuiyun; Zhou, Jiying (Frontiers in Human Neuroscience, 2020)
Previous studies have shown that vestibular migraine (VM) is a cerebral dysfunction disease with recurrent vertigo. Vestibular rehabilitation (VR) is an effective physical therapy for improving the symptoms of vertigo in patients. It mainly accelerates the occurrence of vestibular compensation. But the brain regions that play a role in vestibular migraine are unclear. Resting-state functional magnetic resonance imaging was performed before and after one-month vestibular rehabilitation in 14 patients with vestibular migraine. Low-frequency amplitude fluctuations (ALFF) were assessed to characterize the spontaneous brain activity. Correlations between clinical characteristics and ALFF values were analyzed. We found that compared with baseline, after one month of VR training, the ALFF value of the left posterior cerebellum of VM patients increased significantly. Moreover, the increase in ALFF values in the left cerebellum was inversely correlated with the patient's Dizziness Handicap Inventory (DHI) scores. The study showed the benefits of vestibular rehabilitation on VM patients. Cerebellar hyperactivity is a functional compensation for vestibular dysfunction, but there is asymmetry.